2021
DOI: 10.1186/s12864-021-08086-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sheep lncRNAs related to the immune response to vaccines and aluminium adjuvants

Abstract: Background Long non-coding RNAs (lncRNAs) are involved in several immune processes, including the immune response to vaccination, but most of them remain uncharacterised in livestock species. The mechanism of action of aluminium adjuvants as vaccine components is neither not fully understood. Results We built a transcriptome from sheep PBMCs RNA-seq data in order to identify unannotated lncRNAs and analysed their expression patterns along protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Though, in encephalon, the response was very mild, and a greater gene alteration was observed in sheep treated only with aluminum hydroxide. We also analyzed the differentially expressed lncRNAs in both tissues ( 9 , 10 ), and it was observed that many immune-related lncRNAs were deregulated in PBMC after repetitive vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Though, in encephalon, the response was very mild, and a greater gene alteration was observed in sheep treated only with aluminum hydroxide. We also analyzed the differentially expressed lncRNAs in both tissues ( 9 , 10 ), and it was observed that many immune-related lncRNAs were deregulated in PBMC after repetitive vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…The annotation and functional characterisation of livestock lncRNAs is essential, since most trait-associated variants in livestock lie within non-coding genome regions ( Weikard et al, 2017 ). In sheep, lncRNAs have been profiled across a multi-tissue dataset ( Bush et al, 2018 ), but there are few functional studies investigating their involvement in the immune response and those are difficult to compare due to differences in naming and data availability ( Jin et al, 2018 ; Bilbao-Arribas et al, 2021 ; Chitneedi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%